Effect Of Zinc Borate And Filler Loading On The Properties Of Post Biodegradation Meranti Wood Flour Filled Recycled High Density Polyethylene (rHDPE) Composite - Samsir, Norhazariah (2011)
The aim of this study was to investigate the effect of wood loading and effect of Zinc Borate (ZB) on strength on wood plastics composite (WPCs) properties via soil burial and agar block test. WPCs consisting recycled high density polyethylene (rHDPE), ZB and meranti wood flour (WF) were compounded by twin screw extruder then molded using injection molding and compression molding into flexural shape samples. In order to study the effect of ZB, the composite samples were exposed to brown rot, Gloeophyllum Trabeum (GT) or white-rot fungus, Corilous Versicolor (CV) up to 12 weeks. The composite also used for field soil burial up to 48 weeks at Universiti Sains Malaysia, Nibong Tebal.